Desafios das mudanças nos procedimentos da gestão empresarial: estudo de caso de empresa de manufatura - Oliveira, Priscilla Moraes de (2010)
Organizations need to win the challenges of increasing macroeconomic forces of globalization and market competition, the requirements of government regulations and expectations of society. They are driven to improve the quality of their products and services with a corresponding cost reduction, innovation to boost growth, in addition to need more and more transcend the issues targeted purely by business for a performance conducted by the pursuit of economic sustainability, social environmental in a integrated way. To fit the complex reality present and future, organizations need to implement a new management procedure that facilitates the strengthening of strategies and their better dissemination throughout the structure. One line of research that concentrates its efforts in this field of knowledge is called the strategy execution culture, by Bossidy and Charan, by Hrebiniak and by other authors, which is based on establishing clear goals and strategies, with the division into all levels, in order to emphasize the crucial tasks of each employee to the goals and objectives of strategies to be achieved. Although it is known that many companies are deploying world-culturebased procedures for implementing the strategy, there are few scientific studies that contribute to better understanding and guidance on the execution and results, particularly in the Brazilian context, in which until 2009 had only a company in the deployment process. Given the importance and while the lack of information about the purpose of this paper is to study the concepts, factors influence the results and challenges arising from changes brought about in an organization, with the implementation of management procedures based the culture of the strategy. The work involved conducting a case study of the A.W. Faber-Castell S.A. that have implemented management procedures based on the strategy execution culture to carry out desk research combined with interviews, literature review, personal observations and other forms of gathering and analyzing information. Emphasis is given to the study of semiquantitative indicators and qualitative data on corporate strategy, the process of internal communication and leadership as a way of understanding their influences and outcomes, individual and synergistic effects associated with changes in management procedures. The main bottlenecks identified, the possible reasons and opportunities for improvement are also analyzed, including aspects related to social and environmental responsibility.